The Molecular Information About Deadwood Bacteriomes Partly Depends on the Targeted Environmental DNA - Probst, Maraike; Ascher-Jenull, Judith; Insam, Heribert; Gómez-Brandón, María (Frontiers in Microbiology, 2021)
Microbiome studies mostly rely on total DNA extracts obtained directly from environmental samples. The total DNA consists of both intra- and extracellular DNA, which differ in terms of their ecological interpretation. In the present study, we have investigated for the first time the differences among the three DNA types using microbiome sequencing of Picea abies deadwood logs (Hunter decay classes I, III, V). While the bacterial compositions of all DNA types were comparable in terms of more abundant organisms and mainly depended on the decay class, we found substantial differences between DNA types with regard to smaller operational units. Our findings provide evidence of an increased ecological depth of analysis when considering the intra- and extracellular DNA fractions compared to the total DNA pool. Both DNA fractions were comparable in proportions and the extracellular DNA appeared to persist in the P. abies deadwood logs, thereby enabling its masking effect. Indeed, the extracellular DNA masked the compositional dynamics of intact cells in the total DNA pool. Moreover, the differential analysis of the DNA types underlined the relevance of N2-fixation for P. abies deadwood decomposition and revealed that the role of Acidobacteria under this scenario might be underestimated, especially compared to Actinobacteria.